Comparative analysis of match duration and footballers running performance: 2022 FIFA world cup vs. 2018 FIFA world cup - Zhai, Y.; Wang, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This study aims to explore differences in match duration and player running between the 2022 FIFA World Cup and the 2018 FIFA World Cup , investigate the relationship between match duration and running distance, and discuss the implications of the 2022 extra time reform on future football-specific fitness training. METHODS: Video replays of 64 matches from the 2018 and 2022 FIFA World Cups were meticulously analyzed. Match time data for the first and second halves, as well as extra time, were recorded based on referees whistle signals. Running data for each team in both tournaments were obtained from FIFAs official website and categorized into walking (0-7km/h), low-speed running (7-15km/h), medium-speed running (15-20km/h), high-speed running (20-25km/h), and sprint running (25km/h+). Differential comparisons of time and running data were conducted using IBM SPSS Statistics 19, and Pearson correlation analyses were performed between time and running data. RESULTS: Match Duration: The average match duration per match was significantly higher in the 2022 FIFA World Cup compared to the 2018 FIFA World Cup (103.90±9.219 vs. 99.45±8.702 minutes, p<0.05, Cohens d=0.50). The average effective playing time per match in 2022 was 58 minutes 04 seconds, higher than 55 minutes 09 seconds in 2018. Statistically significant differences were observed in match durations for the first and second halves, while overtime duration showed no statistical significance. Differences in match durations were significant in the group stage matches but not in the knockout stage. Footballers Running Performance: In terms of team average total distance run per match, 2022 was significantly higher than 2018 (114603±433.16 vs 104662±376.17 meters, p<0.05, Cohens d=24.51). Similarly, team average per-match high-intensity running distance (speed =20km/h)(9170.87±821.38 vs 7554.37±574.35 m , p<0.05,Cohens d=2.28)and distance per sprint (speed =25km/h)(2389.94±302.61 vs 2026.03±230.99 m , p<0.05,Cohens d=1.35) were significantly higher in 2022 compared to 2018. The team average number of sprints per match in 2022 was also significantly higher than in 2018(528±40 vs 330±24 , p<0.05,Cohens d=6.00). Correlation Analysis: In 2022, there was a very large positive correlation between match duration and total team distance run per match (r=0.834, p<0.05), a moderate positive correlation for both high-intensity running (r=0.477, p<0.05) and sprinting distance run (r=0.403, p<0.01), and a large positive correlation for the number of sprints (r=0.570, p<0.05), all statistically significant. CONCLUSION: The reform of extra time regulations in football matches significantly increased match duration in the 2022 FIFA World Cup compared to the 2018 FIFA World Cup. Players were required to cover longer distances with higher intensity and engage in more sprints during matches, highlighting increased demands on players physical fitness, especially anaerobic endurance.